Solid waste management in urban Brazilian Northeast (Research, Society and Development, 2021)
Solid waste is one of the disposable materials widely used throughout the urban Northeast, and it has an essential value for the consuming public, its use requires responsibility and awareness in handling. Data provided by the National Confederation of Municipalities (CNM) dumps observatory estimate that there are about 898 in numbers of dumps and landfills controlled in the Northeast region. In this article we will focus on solid waste from the microregions of Paraíba and Ceará. And so, point out guidelines for the provisions of Federal Law No. 12,305/2010 that instituted the PNRS. Can be used in practice. These guidelines stipulate the deadline for municipalities, highlight the techniques used, the importance of planning, concern with the financial aspect, organize dates, contribute to the formation of ideas, guide safety practices, at the same time, the reality in the context solid waste management requires the adoption of a holistic perspective, which provides a critical and reflective look at the conscientious use of waste, in order to minimize social and environmental impacts. With the study, it was possible to verify the need for effective public policies, and the adoption of an institutional policy, curriculum adoption in schools through more information, this is possible through educational advertising, and also through knowledge forums with the aim to provide greater awareness of the problem, and thus mitigate impacts and provide the adoption of effective strategies. Through the aforementioned actions, the generation of jobs will be positively impacted, and there will be greater environmental awareness, the adoption of these measures also contributes to health, as incorrect disposal generates impacts on the health of the populations studied. Given the context, projects and practices are important challenges for the future, but changes require the implementation of solid waste management with the populations studied.